"Who Wants to Know all this Stuff?!": Understanding Older Adults' Privacy Concerns in Aged Care Monitoring Devices. Issue 5 (24th November 2021) - Alkhatib, Sami; Kelly, Ryan; Waycott, Jenny; Buchanan, George; Grobler, Marthie; Wang, Shuo
Abstract: Aged care monitoring devices (ACMDs) enable older adults to live independently at home. But to do so, ACMDs collect and share older adults' personal information with others, potentially raising privacy concerns. This paper presents a detailed account of the different privacy problems in ACMDs that concern older adults. We report findings from interviews and a focus group conducted with older adults who are ageing in place. Using Daniel Solove's privacy taxonomy to categorize privacy concerns, our analysis suggests that older adults are concerned about the potential for ACMDs to give rise to six problems: surveillance, secondary use of data, breach of confidentiality, disclosure, decisional interference and disturbing others. Other findings indicate that participants are worried about their ability to impose control over collection and management of their personal details and are willing to only accept privacy trade-offs during emergencies. We provide recommendations for ACMD developers and future directions to address findings from this research.